Hegemonic Formations and prison thresholds in the interactive dynamics of jails. The case of the Penitentiary Unit nº 3 in the city of Rosario (Argentina) - Manchado, Mauricio (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This work aims to investigate about the communication and subjective process produced in the prison, starting to ask if it is posible the formation of hegemonic relations in the jail, particularly, in Penitentiary Unit nº 3 in the city of Rosario – in wich case we focus our research -. For that, we will examinate how “present” or built there the antagonism, borders, identities, the excluded item - “constitutive outside”- , the signifier/s vacuum/s and the differents logics – differential and equivalential– as conditions of hegemonic formations, according to the perspectives of Ernesto Laclau and Chantal Mouffe. We also propose interbreed and stress this analysis with interactions produced between the locked subject and the others stakeholdersof the daily jail; interactions that, we hold, are formed in processes similars to the formation of hegemonic relations. Therefore, that crossing – theoretical and analytical – aims, finally, think the link between comunication processes, conflict in prisons and the subjective construction of who inhabit the prisons of Santa Fe.